The star formation history and the nature of the mass–metallicity relation of passive galaxies at 1.0 < z < 1.4 from VANDELS. Issue 2 (23rd January 2023) - Saracco, P; Barbera, F La; De Propris, R; Bevacqua, D; Marchesini, D; De Lucia, G; Fontanot, F; Hirschmann, M; Nonino, M; Pasquali, A; Spiniello, C; Tortora, C
ABSTRACT: We derived stellar ages and metallicities [Z/H] for ∼70 passive early-type galaxies (ETGs) selected from VANDELS survey over the redshift range 1.0 < z < 1.4 and stellar mass range 10 < log( M * /M⊙ ) < 11.6. We find significant systematics in their estimates depending on models and wavelength ranges considered. Using the full-spectrum fitting technique, we find that both [Z/H] and age increase with mass as for local ETGs. Age and metallicity sensitive spectral indices independently confirm these trends. According to EMILES models, for 67 per cent of the galaxies we find [Z/H] > 0.0, a percentage which rises to ∼90 per cent for log( M * /M⊙ ) > 11 where the mean metallicity is [Z/H] = 0.17 ± 0.1. A comparison with homogeneous measurements at similar and lower redshift does not show any metallicity evolution over the redshift range 0.0 < z < 1.4. The derived star formation (SF) histories show that the stellar mass fraction formed at early epoch increases with the mass of the galaxy. Galaxies with log( M * /M⊙ ) > 11.0 host stellar populations with [Z/H] > 0.05, formed over short time-scales (Δ t 50 < 1 Gyr) at early epochs ( t form < 2 Gyr), implying high star formation rates (SFR > 100 M⊙ yr −1 ) in high-mass density regions (log(Σ1kpc ) > 10 M⊙ /kpc 2 ). This sharp picture tends to blur at lower masses: log( M * /M⊙ ) ∼ 10.6 galaxies can host either old stars with [Z/H] < 0.0 or younger stars with [Z/H] > 0.0, depending on the duration (Δ t 50) of the SF. The relations between galaxy mass, age, and metallicities are therefore largely set up ab initio as part of the galaxy formation process. Mass, SFR, and SF time-scale all contribute to shape up the stellar mass–metallicity relation with the mass that modulates metals retention.